Exploring Social Media Addiction In University Students An Empirical Research - Akther, Fatima (Green Publisher Indonesia, 2023)
The study aimed to explore the prevalence and factors associated with social media addiction among university students. The study utilized a quantitative research approach, utilizing a survey questionnaire to gather data from a sample of university students (n=90). The study sample consisted of students from various faculties and years of study. The findings indicate that a significant percentage of university student’s exhibit symptoms of social media addiction, such as compulsive social media use, withdrawal symptoms, and negative consequences associated with their social media usage. In addition, students who spent more time on social media platforms were found to have a higher risk of social media addiction. Furthermore, the study identified several factors contributing to social media addiction, including the need for social validation, peer pressure, and boredom. The study results highlight the importance of addressing social media addiction among university students, as it can have negative impacts on academic performance, mental health, and social well-being. The study recommends that universities and policymakers should develop interventions to promote healthy social media use habits and provide support for students struggling with social media addiction. This study provides valuable insights into the prevalence and factors associated with social media addiction among university students. The findings underscore the need for awareness, education, and interventions to promote healthy social media use habits among university students. This study contributes to the growing body of research on social media addiction and provides valuable information for policymakers, educators, and mental health practitioners.